G Protein-Coupled Estrogen Receptor Regulates Actin Cytoskeleton Dynamics to Impair Cell Polarization - Lachowski, Dariusz (Front Cell Dev Biol, 2020)
Mechanical forces regulate cell functions through multiple pathways. G protein-coupled estrogen receptor (GPER) is a seven-transmembrane receptor that is ubiquitously expressed across tissues and mediates the acute cellular response to estrogens. Here, we demonstrate an unidentified role of GPER as a cellular mechanoregulator. G protein-coupled estrogen receptor signaling controls the assembly of stress fibers, the dynamics of the associated focal adhesions, and cell polarization via RhoA GTPase (RhoA). G protein-coupled estrogen receptor activation inhibits F-actin polymerization and subsequently triggers a negative feedback that transcriptionally suppresses the expression of monomeric G-actin. Given the broad expression of GPER and the range of cytoskeletal changes modulated by this receptor, our findings position GPER as a key player in mechanotransduction.